Slovak-Korean Cultural Standards in the Work Environment - Bombekova, Anna (2025)
The bachelor's thesis focuses on Slovak-Korean cultural standards in the work environment. The aim of this bachelor’s thesis is to identify cultural standards within a work environment shared by Slovaks and Koreans using primary and secondary data and to formulate recommendations for Slovaks working with Koreans. This thesis has two partial aims. The first partial aim is to identify key factors influencing successful cross-cultural cooperation in the workplace. The second partial aim is to identify key cultural differences that could lead to potential conflicts in the workplace shared by Slovaks and South Koreans. The methodology integrates secondary research using the cultural dimension models of Geert Hofstede and Fons Trompenaars with primary qualitative data collected via the Critical Incident Method by Alexander Thomas. The primary research was conducted through 12 in-depth interviews with Slovak professionals who have worked with South Korean partners for at least half a year. The study successfully identified five major areas of cultural differences and potential conflicts in the workplace: hierarchy and age-based authority, mandatory collective participation, workplace contribution measurement (prioritizing presence over output), procedural rigidity combined with timing flexibility, and contrasting communication and relationship-building styles. Finally, based on the results of the research and on secondary sources, recommendations for Slovaks in working relationships with Koreans are proposed.